The Impact of Translation Method and Shift on Translation Quality at Bilingual Textbooks of Physics, Mathematics and History - Kammer Tuahman Sipayung (Lingua Cultura, 2020)
The first goal of the research was to figure out translation methods and shifts applied in translating bilingual textbooks of History, Mathematics, and Physics, Those bilingual textbooks were published by Quadra, Yramawidia, and Yudhisthira, used for grade seven in Medan. The second was to figure out the impact of translation methods and shifts which dominant on translation quality. The third was to recommend better bilingual textbooks to use based on the translation quality point of view. The research used a descriptive qualitative research method with a questionnaire, depth-interview, and observation on a pair of translation to collect the data. The data were analyzed with interactively and non-interactively. Based on the data analysis, the research finds that (1) the dominant shift on History textbook is unit shift while the dominant method is a free translation, the dominant shift on Physics is a unit shift and dominant method is a communicative translation, the dominant shift on Mathematics is structure shift and dominant method is communicative translation. The second finding is that the impact of the dominant translation shift and method on the History textbook is negative. At the same time, in Mathematics and Physics are positive. Third, the research; the researcher recommends bilingual textbooks of Mathematics and Physics to use based on translation quality point of view. The well bilingual textbooks can improve students’ language skills, while low translation quality influences bad development to students on learning the language.